Suitability of dynamic environments in virtual reality for schizophrenia therapies - Deusdado, Leonel (2023)
Serious Games (SG) have a significant positive impact on a wide range of purposes. Serious virtual games focused on the rehabilitation of schizophrenia are able to bring improvements to patients who require constant and individualized rehabilitation. Schizophrenia is a mental illness that has no cure and requires intensive rehabilitation for symptoms relief. Virtual Reality (VR) has gained acceptance in the medical field for a variety of rehabilitation by virtue of its immersiveness and versatility. Virtual environments can assist this process, seeking to contemplate important topics for their daily lives, facilitating the understanding of their situation and difficulties. To achieve more effective results, a virtual scenario must be dynamic and suitable to each patient. Nonplayable Character (NPC), which in this work can be human-like or pet-like representations, tasks, varied and objective interactions, and the ambiance all play an important role in determining the expected result. The work described in this paper approaches previously mentioned topics by investigating the contribution of previous works in this context for approaching multiple elements that control the dynamic environment, bringing new modalities and research for the development of a SG for VR focused on the rehabilitation of schizophrenia by facilitating schizophrenics’ daily lives.